Baby animals playing - Eszterhas, Suzi (Eszterhas, Suzi. Baby animals series., 2017)
"The first in a new series, this book showcases ten species from three continents, each engaged in different forms of play. Stunning, intimate, full-color photographs by Suzi Eszterhas are each paired with a short sentence highlighting information about the animal. Designed both as a read-aloud and for young children to explore independently, this book will encourage readers to make connections between themselves and the animals. Back matter gives further information about Suzi Eszterhas and her wildlife photography work."--